The effects of globalization on wage inequality: New insights from a dynamic trade model with heterogeneous firms - Sebastian Braun; Wolfgang Lechthaler; Mariya Mileva (Kiel Institute for the World Economy (IfW), 2014)
Fears of increasing inequality play a dominant role in current debates on how globalization is affecting our economies. After a brief review of recent trends in wage inequality, this policy paper presents new insights on the dynamic effect of trade liberalization on wage inequality. In the context of a dynamic trade model with costly labour mobility (Lechthaler and Mileva, 2013), we show that the effect of trade liberalization on wage inequality depends on i) the time horizon considered, ii) the degree of worker mobility, and iii) the degree of trade liberalization (partial/full). In the short-run, observed increases in wage inequality are driven by an increase in inter-sectoral wage inequality, while in the long run, wage inequality is driven by an increase in the skill premium.
Keywords: 330